If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-4)(u + 2) = ((3)(2u + 4)) + 4 Reorder the terms: -4(2 + u) = ((3)(2u + 4)) + 4 (2 * -4 + u * -4) = ((3)(2u + 4)) + 4 (-8 + -4u) = ((3)(2u + 4)) + 4 Reorder the terms: -8 + -4u = (3(4 + 2u)) + 4 -8 + -4u = ((4 * 3 + 2u * 3)) + 4 -8 + -4u = ((12 + 6u)) + 4 -8 + -4u = (12 + 6u) + 4 Remove parenthesis around (12 + 6u) -8 + -4u = 12 + 6u + 4 Reorder the terms: -8 + -4u = 12 + 4 + 6u Combine like terms: 12 + 4 = 16 -8 + -4u = 16 + 6u Solving -8 + -4u = 16 + 6u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-6u' to each side of the equation. -8 + -4u + -6u = 16 + 6u + -6u Combine like terms: -4u + -6u = -10u -8 + -10u = 16 + 6u + -6u Combine like terms: 6u + -6u = 0 -8 + -10u = 16 + 0 -8 + -10u = 16 Add '8' to each side of the equation. -8 + 8 + -10u = 16 + 8 Combine like terms: -8 + 8 = 0 0 + -10u = 16 + 8 -10u = 16 + 8 Combine like terms: 16 + 8 = 24 -10u = 24 Divide each side by '-10'. u = -2.4 Simplifying u = -2.4
| 10=-4v-v | | [3z-2]+5=9 | | (f/2)-4=1 | | 112+2x=22-4x | | 2[4x+1]-5=1 | | -24=2x-x+6 | | p+9=0 | | 1/2[2x-1]-3=1 | | 9x^5/27x^2 | | 270/3[(4-3)3-(-9)]-53 | | 3(y-2)+2y+5=9y-4+3y+1 | | -132+(-7)=-139 | | k+5=-5 | | -7x-83=29-3x | | x-9y=-39 | | g(x)=-9-5x | | 4x-2+3=7x+x+14 | | 2n-4.5+n=13.5 | | 3.5x-20=2.5x+13 | | 2x-8-4= | | -3/4=1/4u-4/3 | | 8-2x+2=6 | | 3(x-1)+4x=-10 | | 23x^2-92=0 | | -35=x-3x-27 | | 3(x-1/2)-1/4(x-1/3)=1/3 | | 45x-105x^2=0 | | -48=9x+24-5x | | v=1/3bhv=10,h=2 | | x+(x*2)+(x*2)-1=149 | | 5/7=x/3 | | 4n-7=-63 |